Potential Energy Surfaces of Vinylogous Wolff Rearrangement: NBO Analysis and Molecular Dynamic Simulation. Issue 10 (6th August 2021) - Nahzomi, Hossein Taherpour; Divsar, Faten
Abstract: The potential energy surfaces of the Vinylogous Wolff Rearrangement, an alternative process for the Wolff Rearrangement that takes place β, γ‐unsaturated diazoketones have been fully explored employing M062X model chemistry and in a complementary task by means of the CASSCF method. The NBO analysis has been invoked to reveal the alternations of orbital occupancies and their stabilization energies through some of the critical structures located on the pathways. The calculations establish a two steps process for each pathway involving a second higher energy transition state that seems likely to be the rate determining step in agreement with experimental results. Energy analysis indicates more feasibility of the pathway including diradical intermediate. The most striking feature of the study concerns the finding out a transition state providing a channel in between two pathways through interconversion of the two keys bicyclo[2.1.0]pentanone and diradical intermediates. Abstract : Two competing reaction pathways of Vinylogous Wolff Rearrangement of β, γ‐Unsaturated α'‐Diazo Ketone into of β, γ‐Unsaturated Ketene have been explored. The calculations establish a two steps rearrangement for each pathway. The very low energy barriers for first transition states are remarkable. The second step of pathway B has lower energy barrier than pathway A. The interconversion of the two intermediates investigated and reasoned that the conversion of bicyclo[2.1.0] pentanone into diradical requires 8.09 Kcal mol −1 to be proceed.